2020
DOI: 10.1371/journal.pone.0240360
|View full text |Cite
|
Sign up to set email alerts
|

Identifying critically ill children at high risk of acute kidney injury and renal replacement therapy

Abstract: Acute kidney injury (AKI), a common complication in paediatric intensive care units (PICU), is associated with increased morbidity and mortality. In this single centre, prospective, observational cohort study, neutrophil gelatinase-associated lipocalin in urine (uNGAL) and plasma (pNGAL) and renal angina index (RAI), and combinations of these markers, were assessed for their ability to predict severe (stage 2 or 3) AKI in children and young people admitted to PICU. In PICU children and young people had initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In our cohort, RA positivity was 20.5% at baseline, similar to other studies (17.9 to 22.5%) that had enrolled patients with respiratory and post-operative conditions as the indication for PICU admission [ 13 , 29 ]. In contrast, two American studies by Gorga et al.…”
Section: Discussionsupporting
confidence: 86%
“…In our cohort, RA positivity was 20.5% at baseline, similar to other studies (17.9 to 22.5%) that had enrolled patients with respiratory and post-operative conditions as the indication for PICU admission [ 13 , 29 ]. In contrast, two American studies by Gorga et al.…”
Section: Discussionsupporting
confidence: 86%
“…The study showed a sensitivity of 88%, a specificity of 58%, a PPV of 24%, an NPV of 97%, and an AUC of 0.73. However, when the author combined RAI with a biomarker, NGAL, the AUC was 0.80, suggesting a higher association in predicting severe AKI in PICU patients ( 17 ). Similarly, another recent study by Raman et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present meta-analysis by Meena et al [24], combination of urinary NGAL with RAI positivity was found to have better specificity of prediction of severe AKI. Individually plasma NGAL has been found to have lower predictive ability than urinary NGAL and RAI, but in combination with RAI, they have better prediction for severe AKI [28]. Basu et al [29] studied discrimination of plasma NGAL, matrix metalloproteinase-8 (MMP-8) and neutrophil elastase-2 (Ela-2), determined individually and in combination with the RAI for severe AKI in children with sepsis.…”
Section: Clinical Applicationmentioning
confidence: 99%